Perancangan Strategi Sistem Informasi untuk Meningkatkan Daya Saing UMKM Digital: Studi Kasus Cafe Cold N Brew Purwokerto - Anugrah Bagus; Zhafran Mahardika; Bathin Daffa Ramadhan; Gustin Setyaningsih (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
This study aims to analyze the implementation of information systems and formulate information system strategies at Café Cold N Brew Purwokerto. The café has implemented a digital cashier system to support its daily business operations. A qualitative method with a case study approach was employed, using data collected through interviews with café management and documentation. The findings indicate that Café Cold N Brew utilizes the Hyperpos digital cashier system, supported by Microsoft and developed internally, which is integrated across branches and supports cashless transactions. The system improves transaction speed, sales recording accuracy, and business data management. However, operational activities remain dependent on internet connectivity and the central server. Analysis using the McFarlan Strategic Grid places Hyperpos in the Key Operational quadrant, indicating its critical role in daily operations despite not yet providing strategic differentiation. Value Chain analysis shows that the system mainly supports operational activities, inbound logistics, firm infrastructure, and technology development. The recommended strategy includes improving network and server stability, integrating inventory management, developing sales analysis features, and expanding system utilization to marketing and customer service. These improvements are expected to strengthen decision-making and enhance the café’s competitiveness.